Becoming audible sounding animality in performance - McQuinn, Austin, 1967- (Animalibus ;, 2021)
Becoming Audible explores the phenomenon of human and animal acoustic entanglements in art and performance practices. Focusing on the work of artists who get into the spaces between species, Austin McQuinn discovers that sounding animality secures a vital connection to the creatural.To frame his analysis, McQuinn employs Gilles Deleuze and Félix Guattari's concept of becoming-animal, Donna Haraway's definitions of multispecies becoming-with, and Mladen Dolar's ideas of voice-as-object. McQuinn considers birdsong in the work of Beatrice Harrison, Olivier Messiaen, Céleste Boursier-Mougenot, Daniela Cattivelli, and Marcus Coates; the voice of the canine as a sacrificial lab animal in the operatic work of Alexander Raskatov; hierarchies of vocalization in human-simian cultural coevolution in theatrical adaptations of Franz Kafka and Eugene O'Neill; and the acoustic exchanges among hybrid human-animal creations in Harrison Birtwistle's opera The Minotaur. Inspired by the operatic voice and drawing from work in art and performance studies, animal studies, zooarchaeology, social and cultural anthropology, and philosophy, McQuinn demonstrates that sounding animality in performance resonates "through the labyrinths of the cultural and the creatural," not only across species but also beyond the limits of the human.Timely and provocative, this volume outlines new methods of unsettling human exceptionalism during a period of urgent reevaluation of interspecies relations. Students and scholars of human-animal studies, performance studies, and art historians working at the nexus of human and animal will find McQuinn's book enlightening and edifying.